The different morphologies of yeast and filamentous fungi trigger distinct killing and feeding mechanisms in a fungivorous amoeba. (2nd April 2019) - Radosa, Silvia; Ferling, Iuliia; Sprague, Jakob L.; Westermann, Martin; Hillmann, Falk
Summary: Size and diverse morphologies pose a primary challenge for phagocytes such as innate immune cells and predatory amoebae when encountering fungal prey. Although filamentous fungi can escape phagocytic killing by pure physical constraints, unicellular spores and yeasts can mask molecular surface patterns or arrest phagocytic processing. Here, we show that the fungivorous amoeba Protostelium aurantium was able to adjust its killing and feeding mechanisms to these different cell shapes. Yeast‐like fungi from the major fungal groups of basidiomycetes and ascomycetes were readily internalized by phagocytosis, except for the human pathogen Candida albicans whose mannoprotein coat was essential to escape recognition by the amoeba. Dormant spores of the filamentous fungus Aspergillus fumigatus also remained unrecognized, but swelling and the onset of germination induced internalization and intracellular killing by the amoeba. Mature hyphae of A. fumigatus were mostly attacked from the hyphal tip and killed by an actin‐mediated invasion of fungal filaments. Our results demonstrate that predatory pressure imposed by amoebae in natural environments selects for distinct survival strategies in yeast and filamentous fungi but commonly targets the fungal cell wall as a crucial molecular pattern associated to prey and pathogens.